Analysis of trastuzumab therapy's efficacy with or without pertuzumab combination in the metastatic HER2-positive breast cancer an oncology hospital of Pernambuco - Lima, Kaline Nascimento dos Santos; Cruz, Juvanier Romão; Carvalho, Amanda Florentino Fonseca de (Brazilian Journal of Oncology, 2022)
Objectives: To evaluate the efficacy between trastuzumab-only or pertuzumab plus trastuzumab therapies in metastatic HER2-positive breast cancer patients.Material and Methods: At Hospital de Cancer de Pernambuco (HCP), Recife, Brazil, a cross-sectional study was carried out. One hundred seventy-two patients with HER2-positive metastatic breast cancer (BC) were divided into two groups. One group of patients underwent chemotherapy with trastuzumab-only between 2013 and 2016, and another group underwent treatment with pertuzumab plus trastuzumab (P+H) between 2017 and 2020.Results: The median age was 50.4 years (range 25-86) when diagnosed with tumor metastasis. The patients treated with trastuzumab-only had a mortality rate of 13/100 women per year (95% CI: 9.19 to 18.38), and those treated with trastuzumab plus pertuzumab had a mortality rate of 4.14/100 women per year (95% CI: 2.50 to 6.87). The estimated risk ratio (HR) for the trastuzumab-only group was 3.16-fold higher death than the P+H-treated group. The group of patients who evolved into metastasis during follow-up had a risk 3.12-fold higher of death compared to the group in tumor metastases at early diagnosis. In the multivariate analysis, the HR estimate adjusted for the trastuzumab-only treated group was 3.58-fold higher death than the P+H group. The mean follow-up time was three years (15 days to 14.7 years). The estimated mortality rate was 7.73/100 diagnosed women per year (95% CI: 5.80 to 10.3). In the analysis of overall survival (OS), there was a significant difference between the groups treated with trastuzumab-only or P+H (p<0.0001).Conclusion: There are benefits in incorporating new therapies into Brazil's public health network for the treatment of women with metastatic HER2-positive breast cancer, impacting increased OS and better quality of life, even those diagnosed in more advanced stages.
Keywords: Breast neoplasms; Receptor; ErbB-2; Antibodies; Monoclonal